PERLINDUNGAN HUKUM GURU YANG BERHADAPAN DENGAN KASUS HUKUM AKIBAT TINDAKAN PENDISIPLINAN SISWA DI KOTA BAU-BAU - Siti Sumiwati; Safrin Salam; Rizki Mustika Suhartono (Datuk Sulaiman Law Review (DaLRev), 2026)
The enforcement of student discipline by teachers in Indonesia increasingly faces the risk of criminalization, making legal protection for teachers’ immunity rights a significant issue in the field of education. This study aims to analyze the forms of legal protection available to teachers involved in legal disputes arising from student disciplinary actions in Baubau City. The research employed an empirical juridical approach and was conducted at State Senior High Schools 1, 2, and 5 of Baubau City. Data were collected through in-depth interviews with informants selected using purposive sampling, including principals, teachers, guidance and counseling counselors, homeroom teachers, students, parents, and officials of the Indonesian Teachers Association (PGRI) of Baubau City, and were subsequently analyzed using descriptive qualitative methods. The findings indicate that normative legal protection for teachers has been regulated under Law Number 14 of 2005 concerning Teachers and Lecturers, Minister of Education and Culture Regulation Number 10 of 2017, Article 50 of the Indonesian Criminal Code, and further reinforced through Supreme Court Decision Number 1554 K/PID/2013. However, its implementation remains ineffective. All informants understood the existence of normative legal protection, yet expressed doubts regarding its practical enforcement. The study found no regional regulations or mayoral regulations specifically protecting teachers, resulting in a legal vacuum that has generated a deterrent effect in the form of defensive teaching practices. Teachers tend to avoid physical disciplinary measures due to fear of criminalization, while professional organizations are only capable of providing moral support without concrete legal assistance. This condition reflects the tension between child protection and teachers’ immunity rights, which necessitates a restorative justice approach. The study emphasizes the urgency of establishing specific regional regulations and strengthening multi-sectoral synergy among local governments, schools, and teachers’ professional organizations in order to achieve legal certainty and equitable educational quality.